Nanometric distance measurements between Mn(ii)DOTA centers1. Issue 36 (28th September 2015) - Vincent Ching, H. Y.; Demay-Drouhard, Paul; Bertrand, Hélène C.; Policar, Clotilde; Tabares, Leandro C.; Un, Sun
<x xml:space="preserve">Abstract</x> The distance between two Mn(ii)DOTA complexes attached to the ends of polyproline helices of varying lengths was measured by 94 GHz PELDOR spectroscopy with good accuracy demonstrating their effectiveness as spin-labels.